(untitled) (Biodiversitas Journal of Biological Diversity, 2007)
The aims of this study was to know the major component of essential oils of Temu Kunci (Kaemferia pandurata Roxb.) on a different altitude. This research was carried out by method of Stahl destilation at BPTO and GCMS Cromatography at FMIPA UGM for both of from Kerjo (350 m asl) and Jumapolo (450 m asl). The difference of altitude of temu kunciâ€™s lives on, the same of major component of essential oil but the content among them was different. Â© 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: temu kunci, Kaemferia pandurata Roxb., altitude, essential oils.